Immunohistochemical expression of estrogen receptor alpha in benign prostatic hyperplasia and prostatic carcinoma in Iraqi patients - Mohammed, Wafaa R.; Al-obaidie, Salim R.; Al-Ani, Imad M.; Matloup, Enas I.; Al-obaidie, Ahmed S. (Microscopy Society of Singapore, 2018)
The human prostate has a remarkably high incidence of hyperplastic and neoplastic diseases. Benign prostatic hyperplasia( BPH) occur in about 70% of men over 70 years old, and prostatic carcinoma is the second leading cause of cancer related death in men. Prostate cancer is one of the predominant cancers in Iraq. The aim of the study is to evaluate the expression of estrogen receptor alpha in BPH and prostatic carcinoma immunohistochemically and to correlate ER-α expression in prostatic carcinoma (PCa) with Gleason grading system in tissue samples from BPH and PCa patients of Iraqi population. We investigated the localization of ER-α in twenty case of BPH and twenty case of PCa in a retrospective study. Epithelial immunostaining was present in (70%) of PCa and (25%) of BPH while stromal localization was observed in (25%) and (5%) respectively. Among the positive cases of PCa, the highest percentage (35.72%) were Gleason score 8. The increased epithelial immunostaining for ER-α in PCa than in BPH suggest that ER-α may has a role in carcinogenesis of prostate.